English Teachers’ Perspectives on Mother Tongue-Based Multilingual Education (Scholars' Journal, 2022)
Researchers have shown several benefits of MTB-MLE and several challenges in its implementation. In Nepal, language policies are in the state of flux. Therefore, against the theoretical backdrop, this paper is an attempt to find out the perceived differences between MTI and MTB-MLE, outcomes of MTB-MLE, challenges of MTB- MLE and ways to overcome the challenges. The study adopted convenience sampling and semi-structured interview for data generation. It presents a relevant literature that guided the study to reach the conclusions. The study has thematically analysed the data and shown that MTB-MLE is useful to preserve people’s identities, to enable people to cope up with global market, and to preserve the dying languages. Despite the challenges in the implication of MTB-MLE, the study has given the possible ways to overcome the challenges. The study has clearly mentioned its limitations and shown possibilities for further research as well.